2012
DOI: 10.1103/physrevb.85.035202
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric transport properties of CaMg2Bi2, EuMg2Biet al.

Abstract: The thermoelectric transport properties of CaMg2Bi2, EuMg2Bi2, and YbMg2Bi2 were characterized between 2 and 650 K. As synthesized, the polycrystalline samples are found to have lower p-type carrier concentrations than single-crystalline samples of the same empirical formula. These low carrier concentration samples possess the highest mobilities yet reported for materials with the CaAl2Si2 structure type, with a mobility of ∼740 cm 2 /V/s observed in EuMg2Bi2 at 50 K. Despite decreases in the Seebeck coefficie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 43 publications
(41 reference statements)
6
39
0
Order By: Relevance
“…Because of their structural similarity, the three com- 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 In narrow band gap semiconductors at high temperatures and low carrier concentrations the minority carriers reduce the Seebeck coefficient and increase the electrical conductivity. 29 As both holes and electrons carry heat, the overall thermal conductivity increases. 30 These effects can be seen prominently in Figures 3 and 4 in the case of Ti 2 CO 2 because of its narrow band gap, whereas they are small for Zr 2 CO 2 and Hf 2 CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Because of their structural similarity, the three com- 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 In narrow band gap semiconductors at high temperatures and low carrier concentrations the minority carriers reduce the Seebeck coefficient and increase the electrical conductivity. 29 As both holes and electrons carry heat, the overall thermal conductivity increases. 30 These effects can be seen prominently in Figures 3 and 4 in the case of Ti 2 CO 2 because of its narrow band gap, whereas they are small for Zr 2 CO 2 and Hf 2 CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Such a high resistivity is not reasonable when considering the appearance of the 4d and 4f electrons in Eu (33). Inspired by our previous investigation on analogous Bi-based Zintl AMg 2 Bi 2 (A = Ca, Yb) phases, disordered (Ca,Yb, Eu)Mg 2 Bi 2 Zintl phases have been studied in this work.…”
Section: Significancementioning
confidence: 99%
“…Despite the extensive research on Zintl antimonides, analogous Bi-based Zintl materials have received little attention, even given the competitive TE performance of this system. For the CaAl 2 Si 2 -type Zintl phases, the crystal structures of both alkalineearth-based and rare-earth-based AMg 2 Bi 2 (A = Mg, Ca, Sr, Ba, Yb, Eu, Sm) have been reported (32)(33)(34). However, the reported ZT is ∼0.4 in YbMg 2 Bi 2 and ∼0.1 in CaMg 2 Bi 2 and EuMg 2 Bi 2 via melting, grinding, and annealing, not good enough for practical applications.…”
mentioning
confidence: 99%
“…Indeed, as the layer and the interlayer spacing can often be modified independently, the possibility to transform and hopefully tune adequately the electronic and thermal transport properties is real. For instance, this has been proven in layered compounds crystallizing in the CaAl 2 Si 2 structure type [1][2][3][4][5], in the CdI 2 type structures [6][7][8][9], or in the parent misfits compounds [11][12][13]. The study of these layered compounds have shown that it is possible to somewhat decouple the thermal and electronic properties as, in a simple view, the crystalline layers primarily conduct the charge carriers whereas the thermal transport is mainly affected by the content of the interlayer spacing.…”
Section: Introductionmentioning
confidence: 99%
“…HRTEM image of the sample Cu 0.05 TiS 1.5 Se 0 5. showing the local disruption of the periodicity of the stacking of the TiX 2 layers.…”
mentioning
confidence: 99%